2014
DOI: 10.22342/jims.20.1.179.31-35
|View full text |Cite
|
Sign up to set email alerts
|

The Goodness of Long Path With Respect to Multiple Copies of Complete Graphs

Abstract: Abstract. Let H be a graph with the chromatic number χ(H) and the chromatic surplus s(H). A connected graph G of order n is called good with respect to H,The notation tKm represents a graph with t identical copies of complete graphs on m vertices, Km. In this note, we discuss the goodness of path Pn with respect to tKm. It is obtained that the path Pn is tKm-good for m, t ≥ 2 and sufficiently large n. Furthermore, it is also obtained the Ramsey number R (G, tKm), where G is a disjoint union of paths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Certainly, some results provide evidence for that the answer of this question is yes for some F . Sudarsana [14] showed that P n with n ≥ (t − 2)((tm − 2)(m − 1) + 1) + 3 is tK m -good for m and t ≥ 2 be integers. Indeed, the condition on the number of vertices n can not be released completely.…”
Section: Remarksmentioning
confidence: 99%
“…Certainly, some results provide evidence for that the answer of this question is yes for some F . Sudarsana [14] showed that P n with n ≥ (t − 2)((tm − 2)(m − 1) + 1) + 3 is tK m -good for m and t ≥ 2 be integers. Indeed, the condition on the number of vertices n can not be released completely.…”
Section: Remarksmentioning
confidence: 99%
“…By Theorems 3, 2 and 4, we have the assertion. [17]) If m, k ≥ 2 and n ≥ (k −2)((km −2)(m −1)+1)+3, then K a 1 ,a 2 ,...,a m . By Theorems 3, 2 and 4, we have the assertion.…”
Section: Theorem 9 (Pokrovskiymentioning
confidence: 99%
“…The disjoint union of graphs, t i=1 G i , is a graph with the vertex set t i=1 V i and the edge set t i=1 E i ; and if G i G for each i then t i=1 G i = tG. For the definition of Ramsey number, we cite the results proposed by Sudarsana [13], [11], [12]; that is, for graphs G and H, the Ramsey number R(G, H) is the smallest natural number n such that in every red and blue colorings of the edges of the complete graph K n , there is a graph G in K n which is all edges are red or a graph H in K n which is all edges are blue. In the other terminology, a graph F is called (G, H)-free, if F contains no G and F contains no H. Furthermore, we have an equivalent definition of Ramsey number R(G, H), that is, the smallest positive integer n such that there is no (G, H)-free graph on n vertices exists.…”
Section: Introductionmentioning
confidence: 99%
“…The notation tW m discribe a graph with t copies of wheels of order m + 1. Surahmat et al [14] proved that cycle C n is W m -good; Chen et al [6] showed that P n is W m -good for even m and n ≥ m − 1 ≥ 3; P n is tW 4 -good for n ≥ 15t 2 − 4t + 2, t ≥ 1 [13], and Sudarsana [12] recently proved that C n is tK m -good. Meanwhile, S n is not W 6 -good for n ≥ 3 [5].…”
Section: Introductionmentioning
confidence: 99%